Pengembangan Sistem Aplikasi Sido Rabi Wedding Organizer berbasis Web - Nefiana Mey Ipradita; Fajar Pradana; Mahardeka Tri Ananta (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
The development of technology, especially the web can be used as competition in a business world. There are many companies in the field of wedding organizer services such as Sido Rabbi Wedding Organizer that require an appropriate web information technology, this is because business services, especially wedding organizers, require rapid delivery of information and communication. For now At the time of booking process, wedding service packages are still using via telephone (manual) or clients come to the company. In addition, many brides are lazy to go look around the needs of a wedding and compare one by one a wedding vendor's products / services. Therefore the development of a web-based Sido Rabbi Wedding Organizer Application System was developed using the PHP programming language, JavaScript by utilizing the Laravel Framework for back end and using the HTML5 programming language, CSS for making front end. And for data storage using MySql database. In this study using the waterfall method which is only limited to the testing phase. The steps taken are the literature study stage by gathering the foundation of research theory, the stage of data collection by interviewing stakeholders, the needs analysis stage by knowing the needs needed, the design stage as a reference for implementation, the implementation stage of the results of the analysis and system design, the testing phase to check whether the system in accordance with the previous agreement and the stages of conclusions and suggestions that are useful for summarizing the results of all stages carried out. There are 40 functional needs and 1 non-functional requirement at the needs analysis stage. The system functionality testing is done by unit testing strategy, integration and validation with 100% valid results. To test non-functional requirements using compatibility testing where there are 2 critical in 2 different browsers.system uses compatibility testing with the results there are 2 critical issues on 2 different browsers.